2013
DOI: 10.1371/journal.pone.0056892
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Role for the Asymmetric C-Terminal Domain Dimer of Rous Sarcoma Virus Integrase in Viral DNA Binding

Abstract: Integration of the retrovirus linear DNA genome into the host chromosome is an essential step in the viral replication cycle, and is catalyzed by the viral integrase (IN). Evidence suggests that IN functions as a dimer that cleaves a dinucleotide from the 3′ DNA blunt ends while a dimer of dimers (tetramer) promotes concerted integration of the two processed ends into opposite strands of a target DNA. However, it remains unclear why a dimer rather than a monomer of IN is required for the insertion of each rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 50 publications
2
35
0
Order By: Relevance
“…Previous results with RSV IN(1-270) demonstrated that IN with the C-terminal truncation possesses similar properties to those associated with IN(1-286), including robust concerted integration activity using a larger sized (Ͼ1 kb) GU3 substrate (2). We further explored whether IN(1-269) and IN(1-274) displayed different properties than those associated with IN(1-286).…”
Section: Rsv In Tetramer Is Associated Withmentioning
confidence: 94%
See 2 more Smart Citations
“…Previous results with RSV IN(1-270) demonstrated that IN with the C-terminal truncation possesses similar properties to those associated with IN(1-286), including robust concerted integration activity using a larger sized (Ͼ1 kb) GU3 substrate (2). We further explored whether IN(1-269) and IN(1-274) displayed different properties than those associated with IN(1-286).…”
Section: Rsv In Tetramer Is Associated Withmentioning
confidence: 94%
“…In summary, these qualitative analyses demonstrated that each independently isolated trapped SC contained the inhibitor. IN(1-286) is dimeric in solution (28), and RSV IN(1-270) appeared to be a dimer upon SEC analysis (2). A stock solution of IN was diluted to 45 M with running buffer in the absence of DNA prior to chromatography.…”
Section: Inhibition Of Rsv In Concerted Integration By Stis-clinicalmentioning
confidence: 99%
See 1 more Smart Citation
“…PFV IN is soluble (10-15 mg/mL) in 0.2 mol/L NaCl [48,49] while RSV IN is highly soluble (30 mg/mL) in 0.2 mol/L (NH4)2SO4 [50] . PFV IN is monomeric [49] while RSV IN is a dimer in solution [50][51][52] . Recombinant HIV IN has been purified as a monomer, dimer and tetramer [47,53,54] .…”
Section: Solution Properties Of Inmentioning
confidence: 99%
“…There are strong structural similarities in the CCD between HIV, PFV and RSV IN (Figure 2) [47,51,52,57,67,76,77] suggesting that under appropriate conditions the highly soluble RSV IN could also be trapped in the presence of the appropriate oligonucleotide (ODN) substrate and STIs. Assembly of a trapped RSV SC at high IN concentrations (1.5 mg/mL; 45 µmol/L) in solution required the presence of 3' OH recessed viral ODN ranging in sizes (16/18R to 18/20R) and DTG, RAL or MK-2048 [50] (Figure 9).…”
Section: Hiv and Rsv Synaptic Complexes Are Kinetically Stabilized Bymentioning
confidence: 99%